2019
DOI: 10.1002/aoc.4751
|View full text |Cite
|
Sign up to set email alerts
|

Organoruthenium (II) complexes featuring pyrazole‐linked Schiff base ligands: Crystal structure, DNA/BSA interactions, cytotoxicity and molecular docking

Abstract: Half‐sandwiched ruthenium (II) arene complexes with piano stool‐like geometry with the general formula [(p‐cymene)RuClL1] and [(p‐cymene)RuClL2] [where L1 = (Z)‐N′‐((1,3‐diphenyl‐1H‐pyrazol‐4‐yl)methylene)furan‐2‐carbohydrazide and L2 = (Z)‐N′‐((1,3‐diphenyl‐1H‐pyrazol‐4‐yl)methylene)thiophene‐2‐carbohydrazide] were synthesized and characterized. The single crystal X‐ray data revealed that the complexes belong to the same crystal system (monoclinic) with octahedral geometry, where the ruthenium atom is surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 71 publications
0
1
0
3
Order By: Relevance
“…Several studies have reported hydrazone-based compounds that can bind metal ions. Various metal ions, including Al 3+ , Cu 2+ , Ru 2+ , Pd 2+ , and Pt 2+ , can form a hydrazone-metal complex, and thus, may be applied in photochromic systems [39], molecular motors [40,41], proton transfer systems [42,43], bioactive materials [44][45][46][47], etc. Acyl hydrazone derivatives are an especially popular type of hydrazone derivatives for metal ion binding.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported hydrazone-based compounds that can bind metal ions. Various metal ions, including Al 3+ , Cu 2+ , Ru 2+ , Pd 2+ , and Pt 2+ , can form a hydrazone-metal complex, and thus, may be applied in photochromic systems [39], molecular motors [40,41], proton transfer systems [42,43], bioactive materials [44][45][46][47], etc. Acyl hydrazone derivatives are an especially popular type of hydrazone derivatives for metal ion binding.…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, a interação do complexo com o DNA foi vista através dos estudos de docking molecular os quais revelaram que o modo de interação do complexo com o DNA pode ocorrer por meio de uma ligação de hidrogênio existente entre o átomo de hidrogênio do grupo -OH (hmxbato) e o átomo de oxigênio do grupo fosfato da guanina DG10 presente na estrutura de DNA analisada (CARUSO et al, 2012;K.S. et al, 2019).…”
Section: Discussionunclassified
“…Foram consideradas diferenças significativas quando p<0,1 (*), p<0,01 (**) e mais significativas quando p<0,001 (***) e p<0,0001 (****). (CARUSO et al, 2012;GOPALAKRISHNAN et al, 2017;GUPTA et al, 2013;KARAMI et al, 2018;K.S. et al, 2019).…”
Section: Hmxbato Interfere Com a Proliferação E Recuperação De Célulaunclassified
“…Sendo assim, a compreensão das interações com alvos biológicos fundamentais no funcionamento das células tumorais de potenciais agentes antitumorais, como é o caso de complexos de rutênio, é de suma importância para desvendar seus mecanismos de ação e possibilitar um posterior aperfeiçoamento na seletividade desses compostos. Atualmente, estudos teóricos de ancoragem molecular estão sendo uma importante ferramenta para predizer essas interações com biomoléculas, sendo que muitos deles estão coerentes com ensaios experimentais 50,[66][67][68][69]. As fosfinas são ligantes amplamente estudados na Química de coordenação, uma vez que, nas sínteses envolvendo esses ligantes, há a formação de complexos metálicos com estabilidade adicional.…”
unclassified